The Effectiveness of Contextual-based Instructional Materials of Elements of Group 15 For Inorganic Chemistry - Wulandari, Agtri; Dasna, I Wayan; Wonorahardjo, Surjani (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
The purpose of research is determine the effectiveness of teaching materials based contextual elements of group 15 for the course of inorganic chemistry. The research design is one group pretest-posttet only. Subjects were students of Chemistry Education University of Palangka Raya as many as 47 people. Based on the research results, is obtained percentage of graduated postes amounted to 93.6%, mean of  n-gain score is 0,54 (moderate), and the probability value (p) is 0,000, showed no significant difference between the pretest and posttest. Therefore, teaching materials element of group 15 based on contextual for inorganic chemistry course effective to improve student’s learning result. Penelitian ini bertujuan untuk mengetahui efektivitas bahan ajar unsur golongan 15 berbasis kontekstual untuk mata kuliah kimia anorganik. Desain penelitian yaitu one group pretest-posttet only. Subyek penelitian adalah mahasiswa Program Studi Pendidikan Kimia Universitas Palangka Raya sebanyak 47 orang. Berdasarkan hasil penelitian, diperoleh persentase jumlah lulus postes sebesar 93,6%, rata-rata n-gain score sebesar 0,54 kategori sedang, dan nilai probabilitas (p) yaitu 0,000 yang menunjukkan ada perbedaan secara signifikan antara nilai pretes dan postes. Oleh karena itu, bahan ajar unsur golongan 15 berbasis kontekstual untuk mata kuliah anorganik efektif meningkatkan hasil belajar mahasiswa.